PEMBELAJARAN AL-QUR’AN METODE LISBA RIHLATI PADA PROGRAM PPL DI SMP NEGERI 11 TANGERANG SELATAN - Mujiburrohman Mujiburrohman; Akhmad Kharis Kurniawan; Suprihatin (LPPM STAI Nida El-Adabi, 2024)
The Field Experience Practice Program (PPL) is a mandatory activity carried out by students of STAI Nida El-Adabi for a month (February 13th until March 18th 2023). In practice, the PPL which was held at SMP Negeri 11 South Tangerang in PAI learning focused more on learning the Qur'an using the Rihlati LISBA method. This study aims to determine the learning of the Koran using the Rihlati LISBA method, which is one of the leading programs in PPL at SMP Negeri 11 Tangerang Selatan. The method used in this research is descriptive qualitative method with data collection through observation, documentation and interviews. As a result, learning the Qur'an using the LISBA Rihlati method is an effective program in improving students' reading and writing Al-Qur'an (BTQ) skills. Learning the Qur'an using this method is expected to continue to be developed and used as a very important supporting material in Islamic Islamic education learning. During the PPL, there were several supporting factors in learning this method including: adequate curriculum, module books, qualified LISBA Rihlati teachers, and quite complete learning media. There are also inhibiting factors, namely that not all of the students have module books and the teaching teachers of the Rihlati LISBA method are still limited.